MEMAHAMI KEMBALI MAKNA GĀYATRĪ MANTRA SEBAGAI UPAYA TRANSFORMASI DIRI MENJADI PRIBADI YANG BERKESADARAN - Gede Endy Kumara Gupta (UHN IGB Sugriwa Denpasar, 2022)
Gāyatrī Mantra has become an important part of the spiritual practice of Hindu society, where almost every Hindu temple, āśrama/pasraman, and most of Hindu’s family make Gāyatrī Mantra as an important Mantra that is chanted every day. Even though the Mantra has been chanted all the time, many Hindus do not even understand the main meaning/purport contained in the Gāyatrī Mantra. In fact, understanding the meaning of the Mantra that we chant can support the effectiveness of the function of the Mantra, as well as by practicing its sādhana. The Gāyatrī Mantra itself is the Mother of the Vedas and also of all Mantras. As interpreted by Hindu figures, the function of this Mantra is basically to pray to the God in his personification as Sāvitrī to illuminate our consciousness, so that it is hoped that the enlightened consciousness can guide ourselves who have chanted the Gāyatrī Mantra.